2011
DOI: 10.1016/j.physleta.2010.12.081
|View full text |Cite
|
Sign up to set email alerts
|

-dependent hyperfine induced transition rates in an external magnetic field for Be-like 47Ti18+

Abstract: Hyperfine induced 2s2p 3 P 0 → 2s 2 1 S 0 transition rates in an external magnetic field for Be-like 47 Ti were calculated based on the multiconfiguration Dirac-Fock method. It was found that the transition probability is dependent on the magnetic quantum number M F of the excited state, even in the weak field. The present investigation clarified that the difference of the hyperfine induced transition rate of Be-like Ti ions between experiment [Schippers et al., Phys Rev Lett 98, (2007) 033001(4)] and theor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 18 publications
1
18
1
Order By: Relevance
“…This illustrates the difference between our present calculations and the earlier results from [37], shown in the last column, which only included the diagonal F = 0 perturbers. It is clear that the contribution from F = ±1 perturbers is significant for the MIT-hfs probabilities.…”
Section: Measurements Of Hits In the Presence Of Magnetic Fields Incontrasting
confidence: 87%
See 2 more Smart Citations
“…This illustrates the difference between our present calculations and the earlier results from [37], shown in the last column, which only included the diagonal F = 0 perturbers. It is clear that the contribution from F = ±1 perturbers is significant for the MIT-hfs probabilities.…”
Section: Measurements Of Hits In the Presence Of Magnetic Fields Incontrasting
confidence: 87%
“…Since there are magnetic fields associated with storage rings, Li et al [37] investigated the contribution of the magnetic fields to the HIT rate for Be-like Ti and concluded that these effects were too weak at the experimental magnetic flux density of 0.75 T. However, in their calculation they neglected the mixing from the F = 0 perturbers, which could be important for higher field strengths. A first more systematic and complete investigation of what we will label MIT-hfs, the simultaneous inclusion of HIT and MIT to compute transition rates, for isotopes with nuclear spin, is the aim of this work.…”
Section: Competition Between Hit and Mitmentioning
confidence: 99%
See 1 more Smart Citation
“…Magnetic quenching in the TSR has been investigated theoretically by Li et al [20] for the 2s 2p 3 P 0 level in Be-like 47 Ti 18+ . The effect has been found to be insignificant for this specific case.…”
Section: Storage-ring Measurements Of Atomic Lifetimesmentioning
confidence: 99%
“…In addition, the HFI transition rates acquire a dependence on the magnetic quantum number m F of the excited level. Li et al [28] concluded that these effects are too weak at the experimental magnetic flux density of 0.75 T to explain the discrepancy between experimental and theoretical HFI transition rates.…”
Section: Quenching By External Fieldsmentioning
confidence: 99%